2021
DOI: 10.1039/d1se00228g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transfer hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) over Ni/NiO–MC (MC = mesoporous carbon)

Abstract: Ni/NiO-MC (MC=Mesoporous carbon), in which Ni and NiO nanoparticles well distributed on MC, has been successfully synthesized by a pyrolysis of Ni/mesostructured polymer framework precursor prepared via an ion-exchange process...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In a separate study, Liu et al using Ni and NiO supported on mesoporous carbon, observed the TOF of 10.8 h −1 in LA hydrogenation. 64 In our studies, we obtained the TOF values of 27 h −1 for 5 wt% Cu/OMS-2 (Pre-Dep) and 10.6 h −1 for 5 wt% Cu/OMS-2 (Wet-Imp).…”
Section: Resultsmentioning
confidence: 95%
“…In a separate study, Liu et al using Ni and NiO supported on mesoporous carbon, observed the TOF of 10.8 h −1 in LA hydrogenation. 64 In our studies, we obtained the TOF values of 27 h −1 for 5 wt% Cu/OMS-2 (Pre-Dep) and 10.6 h −1 for 5 wt% Cu/OMS-2 (Wet-Imp).…”
Section: Resultsmentioning
confidence: 95%
“… The prominent platform chemical LA, obtained through the hydrolysis of the cellulosic part of biomass, serves as a direct precursor to the production of GVL. Consequently, there has been a significant increase in research and development efforts focused on enhancing the synthesis of GVL from LA. , Furfural (FA) in comparison to levulinic acid holds great promise as a C5 substance for producing GVL, as it can be directly obtained from raw biomass . FA undergoes a transformation to furfuryl alcohol (FOL), which can be hydrolyzed to yield levulinic acid (LA) or levulinic esters (LE) in water or alcoholic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The growing demand for sustainable chemicals and fuels produced by renewable resources has attracted much attention with the overexploitation of fossil energy in recent years. , Biomass, the renewable carbon reservoir, is considered a potential alternative to the depleting fossil feedstocks and expected to achieve the goals of carbon neutrality and low-carbon economy. As one of the highest potential biomass derivatives, levulinic acid (LA) produced by acid hydrolysis of cellulose or hemicellulose can be converted to value-added γ-valerolactone (GVL) via a two-step reaction pathway including hydrogenation and intramolecular dehydration or the opposite reaction sequence (Scheme ). , GVL can be widely utilized as a potential additive to transportation fuels, a green solvent, a food ingredient, and an important intermediate for various fine chemicals. Thus, great endeavors have been devoted to the efficient conversion of LA to value-added GVL in recent years. However, although the efficient production of GVL from LA can be achieved, using precious metal catalysts or rigorous reaction conditions is unavoidable, and the high energy expenditure required in expediting the hydrogenolysis of LA prevents the practical application of these catalysts. Therefore, it is necessary to rationally design highly efficient non-noble metal catalysts that can promote the hydrogenation activity of LA under mild conditions.…”
Section: Introductionmentioning
confidence: 99%